Embriogenesis somatica en dos especies del genero Plantago (Plantago major L. y Plantago hirtella Kunth) - Gonzalez A, J.A.=700 1 Oropeza C, M.; Vargas C, T.E.; De Garcia, E.
(En, Es)
ilus., 11 ref.
Keywords: PLANTAGO; PLANTAS MEDICINALES; EMBRIOGENESIS; EMBRION SOMATICO; VENEZUELA; PLANTAGO MAJOR; PLANTAGO HIRTELLA; LLANTEN; AGRONOMIA TROPICAL